Efektivitas Curcumin Dalam Mengurangi Peradangan Pada Dermatitis Atopik - Helga Pasadena; Santi Widiasari (Pusat Riset dan Inovasi Nasional, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by pruritus, erythema, and impaired skin barrier function. Conventional treatments such as topical corticosteroids and calcineurin inhibitors effectively reduce inflammation but pose potential adverse effects that limit their long-term use. Consequently, natural-based alternatives like curcumin have gained increasing interest. Curcumin, a principal polyphenol in turmeric (Curcuma longa), is known for its anti-inflammatory, antioxidant, and immunomodulatory properties. Its mechanisms in AD involve the inhibition of the NF-κB signaling pathway, downregulation of proinflammatory cytokines (IL-4, IL-13, TNF-α), and enhancement of filaggrin and ceramide production, which are crucial for restoring skin barrier function. This study is a systematic review aimed at evaluating the efficacy of curcumin in alleviating AD-related inflammation based on recent clinical and experimental studies. The meta-analysis revealed that nano-curcumin formulations were more effective than conventional curcumin in reducing atopic skin lesions and transepidermal water loss (TEWL). Additionally, combining curcumin with emollients or essential oils exhibited synergistic effects in improving skin hydration and reducing inflammation. In conclusion, curcumin demonstrates significant potential as an adjuvant therapy for AD; however, further research is required to determine its long-term efficacy and safety profile in clinical applications.